A novel test method for quantifying surface tack of polypropylene compound surfaces (eXPRESS Polymer Letters)
While adhesiveness is required for polymer surfaces in special applications, tacky surfaces are generally undesirable in many applications like automotive interior parts. The tackiness of polymer surface results from a combination of composition and additivation, and it can change significantly in natural or accelerated ageing. Since there is no established, uniform method to characterize surface tack, the major focus of the present work was on the development of an objective quantification method. A setup having a soft die tip attached to a standard tensile tester was developed aiming for correlation to the human sense of touch. Three different model thermoplastic polyolefin (TPO) compound formulations based on a high-impact isotactic polypropylene (iPP) composition with varying amounts and types of anti-scratch additives were used for these investigations. As the surface tack phenomenon is related to ageing and weathering, the material’s examination was also performed after various intervals of weathering. The developed method allows a fast assessment of the effect of polymer composition variations and different additive formulations on surface tack and gives identical rankings as the standardized haptic panel.